Development and Psychometric Properties of Counseling Alliance Inventory-Peer, Rating /Observer Version, Based Computer Assisted Testing - Herdi Herdi; Sunaryo Kartadinata; Agus Taufiq (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2019)
Current studies have consistently found that the excellent performance of counselors and the effectiveness and efficacy of counseling are influenced by counseling alliances that are established between counselor and counselee. For this reason, the existence of a tool accurately measuring the counseling alliance between counselor and counselee-peer rating/observer version is necessary. The purpose of this study is to develop and psychometric exam properties of Counseling Alliance Inventory-Peer Rating/Observer (CAI-PR/O) version based computer-assisted testing. This study used instrument development and standardization procedures—this study’s participants of 61 of pre-service counselors from a Department of Guidance and Counseling in Indonesia. Data were collected using a questionnaire that is CAI-PR/O initial version in the form of a Likert five-level scale. Operationally, data analysis was performed by using Rasch Model version 3.75. The results showed that CAI-PR/O had satisfying psychometric properties, i.e., item measure, item fit order, DIF, person measure, person fit order, variable maps, rating scale, test reliability, person reliability, and item reliability. However, the factor structure still needed to be improved. Further studies are needed to examine the psychometric properties of CAI-PR/O in various socio-demography of participants.